(untitled) (Research, Society and Development, 2021)
This study aimed at approaching the scenario, advances and challenges of seafood consumption in school feeding, in Brazil. A literature review was carried out, covering different types of publications such as articles, books, legislation and documents of several organizations, considering contents structured in three axes: seafood consumption in the world and in Brazil; guidelines related to the use of seafood in school feeding; and the development of seafood-based preparations and acceptability tests with schoolchildren, in Brazil. According to the literature, in the country, the consumption per capita / year of seafood is still lower than the international recommendation (12 Kg per capita / year). Policies have been implemented, seeking to stimulate seafood consumption in the country, while there are challenges from a cultural and operational perspective. However, recent political and economic changes have had a negative impact on this evolution. The introduction of seafood in schools showed to be important, given it encourages the formation of the eating habit to this food, since childhood. As for the studies which developed and evaluated the acceptability of seafood products, it was found that preparations such as fishburger, meatballs and nuggets, or even cakes enriched with fish fillets were well accepted, fitting criteria for insertion in school’s menus. Despite the scenario of setbacks in the country’s food and nutrition policies, studies have indicated a high potential for creating seafood preparations, with high acceptability by schoolchildren.